Optimization and Characterization Studies of Dissimilar Friction Stir Welding Parameters of Brass and Aluminum Alloy 6063 Using Taguchi - Vimal Agarwal; Deepam Goyal; B. S. Pabla; S. C. Vettivel; A. Haiter Lenin (Advances in Materials Science and Engineering, 2023)
This paper focuses on optimizing process parameters such as tool rotating speed, preheat-treated workpiece temperature, traverse speed, and tool pin profile for dissimilar friction stir welding (FSW) of brass and AA 6063. The hardness of the friction stir-welded joint created is measured as a response variable. The Taguchi design of experiments approach was utilized to finalize the experimental strategy, and ANOVA was employed to analyze the data. The best input factors for a better weld and a harder FSW workpiece were predicted. The experimental results show that the input factors influenced the hardness and defects in the welds in the following order: tool rotation speed (28.98%), tool pin geometry (22.30%), travel speed (11%), and temperature of the preheat treated workpiece (10.95%), respectively. Optical microscopy identified three distinct zones: the nugget zone, the thermomechanically affected zone, and the heat-affected zone. The nugget zone had a maximum value of hardness (around a 27% increase) due to the formation of very fine recrystallized grains.